“Masalih al-Mursala” as a technique of deriving law opinions within the system of the Islamic law (Journal of Philosophy Culture and Political Science, 2019)
The article deals with problem of “al-masalih al-mursala” (“the general benefi ts”), the methodological technique most frequently applied by the Muslim scholars in order to derive law opinions within the system of the Islamic law. This technique, which is considered to be one of the most important ones in the Islamic law, enables Muslims to tackle different critical conditions, to consolidate the rule of goodness, to prevent the obnoxious situations from befalling people, and to preserve the dynamism of the Islamic law in the cases when no certain judgment on new situations proceeding from the ever-changing nature of the reality is available in any of the major sources of the Islamic jurisprudence such as Koran, Sunna, Ijma, and Qiyas. Keywords: Islamic law, law methodology, public weal, religious proofs, the rational method.